THE DISTINCTIVE LINGUISTIC FEATURES IN BLURBS AS FOUND IN NON FICTIONS; A STYLISTIC ANALYSIS - Sari, Mezia Kemala (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
This research discusses about the special language style from the comments on the book cover of non fictions based on the using of distinctive linguistic features. The style of language is analyzed from stylistics point of view and put the lexical cohesion, reference and another linguistic elements as the part of distinctive linguistic features to be the analysis focus then reflect it to the function and the effect it brings. The methods are referential and formal. Based on the analyis, it can be found that in the comments of the book cover, generally, include all of the lexical and reference elements. The most significant element that mostly occur is repetition and personal reference. While, another forms such as synonym, general word, super ordinate, collocation, demonstrative and comparative reference occur in less percentage. The purpose of using these elements is in order that the comments of the non fictions‟ book can influence the reader through the choosing features then bring the psychological effect for commercial purposes. Moreover, the effect that it caused for the reader is being influenced the readers‟ thought to be more interested to the book from its dictions or the specific distinctive linguistic features.